2014
DOI: 10.1371/journal.pone.0086599
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis Infection Reduces Regulatory T Cells in Infected Atherosclerosis Patients

Abstract: Increasing evidence has shown periodontal pathogen Porphyromonas gingivalis (P.gingivalis) infection contributes to atherosclerosis (AS) progression. P.gingivalis fimbriae act as an important virulence factor in AS. Regulatory T cells (Tregs) may play a crucial role in autoimmune response during this process. However, whether P.gingivalis infection is associated with Tregs dysregulation during AS is still unknown and the prevalence of different P.gingivalis FimA genotypes during this process is unclear. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 48 publications
3
27
0
Order By: Relevance
“…Accordingly, we have previously detected the presence of periodontal bacterial DNA in the serum and synovial fluid from patients with PD and rheumatoid arthritis (29). In addition, it has been recently reported that P. gingivalis infection is associated with reduced levels of CD4 + CD25 + Foxp3 + Treg cells in the peripheral blood of patients with PD and atherosclerosis (30). However, the possible factor(s) accounting for the diminished frequency of CD69 + Treg cells in patients with inactive PD (compared to those with active disease) observed in this study is an interesting point to be explored in future studies.…”
Section: Discussionmentioning
confidence: 93%
“…Accordingly, we have previously detected the presence of periodontal bacterial DNA in the serum and synovial fluid from patients with PD and rheumatoid arthritis (29). In addition, it has been recently reported that P. gingivalis infection is associated with reduced levels of CD4 + CD25 + Foxp3 + Treg cells in the peripheral blood of patients with PD and atherosclerosis (30). However, the possible factor(s) accounting for the diminished frequency of CD69 + Treg cells in patients with inactive PD (compared to those with active disease) observed in this study is an interesting point to be explored in future studies.…”
Section: Discussionmentioning
confidence: 93%
“…[101]. In vivo and in vitro studies demonstrate the importance of the fimbriae of P. gingivalis to host cell entry and to promote atherothrombotic lesions in experimental models [138]. In vitro experiments have shown certain bacterial strains expressing P. gingivalis hemagglutinin A (HagA) have an increased capability to adhere and enter human coronary artery endothelial cells (HCAEC) [7].…”
Section: Do We Have Evidence That Periodontal Bacteria And/or Bacterimentioning
confidence: 99%
“…Tregs may play a crucial role in autoimmune response during this process. However, whether P. gingivalis infection is associated with Tregs dysregulation during atherosclerosis is still unknown and the prevalence of different P. gingivalis FimA genotypes during this process remains unclear ( Yang et al, 2014 ).…”
Section: Fimbriaementioning
confidence: 99%